ICTV Virus Taxonomy Profile: Closteroviridae - Fuchs, Marc; Bar-Joseph, Moshe; Candresse, Thierry; Maree, Hans J; Martelli, Giovanni P; Melzer, Michael J; Menzel, Wulf; Minafra, Angelantonio; Sabanadzovic, Sead; Report Consortium, Ictv (Journal of general virology, 2020)
Viruses in the family have a mono-, bi- or tripartite positive-sense RNA genome of 13-19 kb, and non-enveloped, filamentous particles 650-2200 nm long and 12 nm in diameter. They infect plants, mainly dicots, many of which are fruit crops. This is a summary of the ICTV Report on the family , which is available at ictv.global/report/closteroviridae.